2013
DOI: 10.1021/je400190f
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Modeling of Liquid–Liquid Equilibrium of Polyethylene Glycol 400, Sodium Phosphate, or Sodium Citrate Aqueous Two-Phase Systems at (298.2, 308.2, and 318.2) K

Abstract: Experimental equilibrium data were obtained for aqueous two-phase systems composed of polyethylene glycol 400 g·mol–1 + sodium phosphate, and polyethylene glycol 400 g·mol–1 + sodium citrate, at T = (298.2, 308.2 and 318.2) K. For the system formed by sodium phosphate, at the studied range, the temperature effect on the position of the binodal curves was not relevant. For the system composed of sodium citrate, the temperature increase caused an expansion of the biphasic region. The efficacy of the salts in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
(34 reference statements)
1
8
0
1
Order By: Relevance
“…From the analysis of the binodal data, it was found that, as the temperature increases, the solubility of PEG increases, i.e., lower temperatures are favorable for the formation of the two phases. This behavior is in agreement with that found by Freire et al (2012) Souza et al (2013) when studying systems formed by PEG 400 and sodium citrate and PEG 400 and sodium phosphate.…”
Section: Phase Diagramssupporting
confidence: 91%
“…From the analysis of the binodal data, it was found that, as the temperature increases, the solubility of PEG increases, i.e., lower temperatures are favorable for the formation of the two phases. This behavior is in agreement with that found by Freire et al (2012) Souza et al (2013) when studying systems formed by PEG 400 and sodium citrate and PEG 400 and sodium phosphate.…”
Section: Phase Diagramssupporting
confidence: 91%
“…Extraction and purification of catechins is a challenging task [22]. [23] which showed a good agreement of less than 1% deviation between measured and literature mass fraction data. The validity of the experimental method for the cloud points was further confirmed by carrying out replicas of the assays at random conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…In the literature, aqueous polymer systems were studied with PPG 400 , random and block copolymers, such as Ultraric PE62 and Pluronics L64 and L35, and PEG 400 , PEG 600 , and PEG 1000 because these compounds present advantages such as regenerability due to thermoseparation efficiency, low or controlled toxicity, nonflammability, and commercial availability …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, aqueous polymer systems were studied with PPG 400 , 37 random and block copolymers, such as Ultraric PE62 38 and Pluronics L64 39 and L35, 40 and PEG 400 , 41 PEG 600 , 42 and PEG 1000 43 because these compounds present advantages such as regenerability due to thermoseparation efficiency, 38 low or controlled toxicity, 44 nonflammability, 45 and commercial availability. 46 However, regarding thermophysical properties for aqueous systems composed by these polymers, density (ρ) measurements were reported for aqueous solutions of PPG 400 , 11,47 L64, 48 PEG 400 , 49−51 PEG 600 , 47,50 and PEG 1000 , 51,52 while no such data were not found for PE62 and L35.…”
Section: Introductionmentioning
confidence: 99%